2015
DOI: 10.4103/0366-6999.161363
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Functional and Radiological Outcomes Between Two Posterior Approaches in the Treatment of Multilevel Cervical Spondylotic Myelopathy

Abstract: Background:Posterior cervical decompression is an accepted treatment for multilevel cervical spondylotic myelopathy (CSM). Each posterior technique has its own advantages and disadvantages. In the present study, we compared the functional and radiological outcomes of expansive hemilaminectomy and laminoplasty with mini titanium plate in the treatment of multilevel CSM.Methods:Forty-four patients with multilevel CSM treated with posterior cervical surgery in Department of Orthopedic Surgery, Beijing Army Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
(13 reference statements)
2
14
0
Order By: Relevance
“…After detailed evaluation of these articles, 47 studies remained for detailed assessment. After applying selection criteria, 10 studies [5,[14][15][16][17][18][19][20][21][22] were selected for analysis ( Fig. 1).…”
Section: Quality Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…After detailed evaluation of these articles, 47 studies remained for detailed assessment. After applying selection criteria, 10 studies [5,[14][15][16][17][18][19][20][21][22] were selected for analysis ( Fig. 1).…”
Section: Quality Of Studiesmentioning
confidence: 99%
“…From these 10 included studies, there were 335 patients who underwent laminectomy and fusion compared to 320 patients who underwent extended laminoplasty. Of these, two studies were prospective randomized trials [17,22] whilst the remainder [5,[14][15][16][18][19][20][21] were retrospective observational studies.…”
Section: Quality Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shamji et al [ 15 ] conducted a nationwide database study on the length and cost of anterior and posterior approaches, and the anterior approach was found to be associated with less hospitalization and lower cost. Lau et al [ 16 ] and Ren et al [ 17 ] reported that the operation time and blood loss associated with ACDF were less than those associated with laminoplasty. This is because it takes a long time to detach the paracervical muscle from the lamina in a laminoplasty, resulting in more blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is initially chosen in the following situations: disease affecting more than three levels, primary posterior pathology, congenital cervical stenosis, or in case of ossification of posterior longitudinal ligament or yellow ligament [11,13,14]. Kyphotic alignment of the cervical spine is a contraindication to this surgery.…”
Section: Posterior Cervical Approachesmentioning
confidence: 99%